JUDICIAL ACTIVISM IN INDONESIA - Rahayu Prasetianingsih (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2020)
The existence of Constitutional Court becomes important as requisite for the rule of law principle and democracy in Indonesia. Amendment of the Constitution by Indonesia National Assembly has chosen to share judicial power held by the Supreme Court and Constitutional Court with the authority to judicial review of legislation to the Constitution. The Constitutional Court as Guardian of the Constitution has its own role in establishing constitutional culture in Indonesia. Commitment to constitutionalism is adistinctive constitutional culture which will also develop the constitution itself. Commitment to UUD 1945 as the limitation to the powers and a guarantee of constitutional rights that must be protected by the Constitutional Court with the authority to review as the implementation of Indonesia constitutionalism. Constitutional culture discuss in this paper is focused on understanding constitutional culture which will affect the implementation of the constitution by